Diseño de una propuesta de mejora para la reposición de inventarios a través de la simulación en la línea de vehículos livianos de una empresa distribuidora de autopartes (2019)
The management of inventories represents a very indispensable economic alternative in the organization of companies that strive to reduce costs and improve their productive efficiency. This management is recognized as a pertinent and effective tool for the good management of the available resources, the improvement of the quality of the service to the clients and why not, to improve the margins of financial sustainability. In this research, the design is shown through a simulation software, a proposal to replenish inventories to integrate rotation analysis based on the ABC categorization and the standardization of maximums and minimums, seeking to keep the products that carry it in the NTS on hand to meet over 85% the requirements of its customers. Among the results, it was possible to verify that the safety inventory is a control variable that directly affects the flow of the supply chain and inventory. Since this depends in turn on the flow of orders and the management of purchases made when applying value of security stocks by the company.